The effect of person-organization fit, person-job fit, and organizational commitment on organizational citizenship behavior: Evidence from employees in the Indonesia public sector - Yeni Fitri Astuti; Diah Astrini Amir (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2023)
This research aims to analyze the effect of person-organization fit, person-job fit, and organizational commitment toward organizational citizenship behavior. The samples in this research were 105 employees in the Indonesian public sector with a minimum period of working in the organization for one year. This study used a quantitative approach. Data was collected via online form. The data analysis used to test the hypothesis is multiple regression analysis with IBM SPSS Statistics 25 software. The results of this study indicated that person-organization fit, person-job fit, and organizational commitment had a positive and significant effect on organizational citizenship behavior.